2015
DOI: 10.1111/bjh.13553
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia in sickle cell anaemia is associated with low haemoglobin: a report of 890 admissions to a tertiary hospital in Tanzania

Abstract: SummaryBacteraemia is a leading cause of morbidity in sickle cell anaemia (SCA), but information from studies in Africa is limited. We evaluated 890 admissions from 648 SCA patients at a tertiary hospital in Tanzania. Bacteraemia was present in 43 admissions (4·8%); isolates included Staphylococcus aureus (12/43; 28%), non‐Typhi Salmonella (9/43; 21%), Streptococcus pneumoniae (3/43; 7%) and Salmonella Typhi (2/43; 5%). Compared to SCA patients without bacteraemia, SCA patients with bacteraemia had significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
2
27
2
Order By: Relevance
“…This is at variance with findings by Makani et al 21 in Tanzania where children with bacteremia were more likely to have a lower hemoglobin concentration compared with those without bacteremia. The reason for this difference may be due to differences in the cohorts in the two studies.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…This is at variance with findings by Makani et al 21 in Tanzania where children with bacteremia were more likely to have a lower hemoglobin concentration compared with those without bacteremia. The reason for this difference may be due to differences in the cohorts in the two studies.…”
Section: Discussioncontrasting
confidence: 96%
“…The low incidence is however in agreement with findings in previous studies in Nigeria and a study in Uganda 3,8,20. A study in Tanzania also revealed a predominance of Staphylococcus aureus and rarity of Streptococcus pneumoniae 21. Reasons that have been attributed to the low incidence of Pneumococcal infections in some African countries include greater difficulty in isolating fastidious organisms like Pneumococcus compared with organisms like Staphylococcus aureus and the possibility of unregulated antibiotic usage in these countries 9,22.…”
Section: Discussionsupporting
confidence: 89%
“…However, because this was a retrospective study it was not possible to determine time from blood collection to incubation, or the volume of blood collected for culture—both known to impact on culture yield and likelihood of contaminants. [26] Nonetheless, the rate of blood culture contamination (3.8% of blood cultures taken and 31% of positive blood cultures) is lower than other studies in sub-Sahara Africa, [7,27] and suggests poor technique is unlikely to have greatly influenced our results.…”
Section: Discussionmentioning
confidence: 59%
“…However, our results are consistent with a recent study in Tanzania, where similar rates of bacteremia (4.8% of admissions) and distribution of pathogens ( S aureus 28%, NTS 21%, S pneumoniae 7%) were identified. [7] Records were unavailable for nearly one-third of potentially eligible cases, and we do not know what affect this missing data had on our results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation